ANALISIS KOMPONEN UTAMA FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PETANI MENGGUNAKAN BENIH PADI INHIBRIDADI KABUPATEN LAMPUNG TENGAH - Nurjannah, Evi; Effendi, Irwan; Yanfika, Helvi (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2013)
This study aims to determine the factors and index comparison of components that form the bases in farmers’ decision of using inhibrida rice seeds in Central Lampung Regency. The method of analysis used in this study is factor analysis using Principal Component Analysis (PCA). The results showed the obtained 13 factors affecting farmer's decision to use Inhibrida rice seeds. These factors were obtained after 3 times analysis processes by eliminating the variables that have MSA value of less than 0.5. The thirteen factors were reduced to four components. Of the four components that had formed on the changes in the form of a reference component (component transformation matrix) shows that there were only two components with comparison index of > 0.5, namely the physical of paddy and external components with the value of 0.623 and 0.628respectively. The physical components of paddy consisted of plant age, plant height, rice flavor, grain weight, and potential yield. The external component comprised of plant endurance and product prices. These components were the bases for choosing Inhibrida rice seeds. Keywords: factor analysis, paddy, perception, Principal Component Analysis, seeds